Designing intelligent healthcare systems, products, and services using disruptive technologies and health informatics - Bagga, Teena; Upreti, Kamal; Kumar, Nishant (Of Amity University); Ansari, Amirul Hasan; Nadeem, Danish (Boca Raton : CRC Press, 2022)
"This book offers both theoretical and practical application-based chapters on Computational Intelligence, IoT, Blockchain, Cloud, and Big Data Analytics and presents novel technical studies on designing intelligent healthcare systems, product, and services. It offers conceptual and visionary works comprising hypothetical and speculative scenarios and will also include recently developed disruptive holistic techniques in healthcare and monitoring of physiological data. The book will also provide metaheuristic computational intelligent based algorithms for analysis, diagnosis, and prevention of disease through disruptive technologies"--
Telemedicine (e-Health, m-Health): Requirements, Challenges and Applications -- Future Risk Analysis In Public Sector During Covid-19 Period 2020 To March 2021 -- Role of Advanced Technologies in Gait Analysis and its importance in Healthcare -- Emerging disruptive technologies and their impact on health informatics -- Scaling Up Telemedicine Systems In India : Moving Toward Intelligent Healthcare Via Disruptions -- A Wearable ECG Sensor for Intelligent Cardiovascular Health Informatics -- Recent Trends in Wearable Technologies, Challenges and Opportunities -- Intelligent Depression Detection System using Effective Hyper-Scanning Techniques -- Design of an Intelligent System for Diabetes Prediction by Integrating Rough Set Theory and Genetic Algorithm -- Blockchain for Healthcare Sector : Application and Challenges -- Blockchain Enabled Secured Medical Supply Chain Management -- Big Data in Healthcare, Technological Implications and Challenges -- An Efficient System for Predictive Analysis on Brain Cancer using Machine Learning and Deep Learning Techniques -- A Review Study on Different Machine Learning Algorithms used for Covid Outbreak Prediction -- Designing of a Rough-PSO based Covid-19 prediction Model -- Transitions in Machine Learning Approaches for Healthcare Sector Applications.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Medical applications; Medical informatics; TECHNOLOGY / Manufacturing; TECHNOLOGY / Industrial Design / Product